Dichlorido{N-[2-(diphenylphosphanyl)benzylidene]isopropylamine-κ2N,P}palladium(II) dimethyl sulfoxide monosolvate - Haleden Chiririwa; Reinout Meijboom; Bernard Omondi (Acta Crystallographica Section E, 2011)
In the title PdII complex, [PdCl2(C22H22NP)]·(CH3)2SO, the PdII atom is coordinated in an NPCl2 coordination sphere by the N(imino) and P(phosphane) atoms of the ligand and by two Cl− ions in a slightly distorted square-planar geometry [r.m.s. deviation = 0.081 (3) Å, plane defined by the four atoms around the Pd atom]. The dimethyl sulfoxide solvent molecules form centrosymmetric dimers due to an intermolecular C—H...O interaction. The crystal structure is further stabilized through two intermolecular C—H...π interactions.